COMMUNICATION STRATEGIES OF POLITICAL PARTIES IN INCREASING ELECTABILITY IN DENPASAR - Pratiwi, Nuning Indah; Murdika, I Ketut Gede Gunawan (E-Journal of Cultural Studies; Vol 17 No 4 (2024): Volume 17 Number 4 November 2024, 2024)
A political communication plan is a comprehensive selection of the actions that will be taken now to further future political objectives. In political communication, you must know the forms: a. political rhetoric, political parties to invite and influence voters to vote for political parties through campaigning. b. Political agitation is used to invite people to vote for and support one of the political parties. c. political propaganda is a campaign that invites and guides the public or voters in accepting a view or value. d. political lobbying, negotiating political parties, and bargaining between parties and the government. e. political action political action in shaping the image or image of a political party. In addition, there are stages of communication strategies: observing problems, planning and making programs, taking communication actions, and evaluating work programs. According to Schorder's theory, political strategy is divided into two parts; offensive strategy (attack) and defensive strategy (defensive). This study employed a descriptive qualitative methodology, and the techniques for gathering data included interviews, document studies, and observation. With the study's results, the communication strategy of political parties in increasing electability has been implemented, but the public response says that political parties only brand candidates from political parties. Keywords : Communication Strategy, political communication, Political Parties